2022
DOI: 10.1210/clinem/dgac176
|View full text |Cite
|
Sign up to set email alerts
|

Early Warning of Ischemic Stroke Based on Atherosclerosis Index Combined With Serum Markers

Abstract: Background Ischemic stroke is a serious public health problem worldwide, threatening human life and health. Atherosclerosis is the cause of stroke. At present, there are few selective indexes that can be used to evaluate atherosclerosis in clinical, mainly relying on the atherosclerotic index. Disturbance of lipid metabolism is considered to be a key event leading to ischemic stroke. Aims The purpose of this study is to disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Particularly abdominal or visceral obesity, is associated with a host of metabolic abnormalities, including insulin resistance, dyslipidemia, and inflammation [27][28][29]. These metabolic disturbances contribute to the development and progression of atherosclerosis, a key contributor to stroke [30,31]. Individuals who are overweight or obese are more likely to develop insulin resistance indicating early impaired glucose metabolism [32].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly abdominal or visceral obesity, is associated with a host of metabolic abnormalities, including insulin resistance, dyslipidemia, and inflammation [27][28][29]. These metabolic disturbances contribute to the development and progression of atherosclerosis, a key contributor to stroke [30,31]. Individuals who are overweight or obese are more likely to develop insulin resistance indicating early impaired glucose metabolism [32].…”
Section: Discussionmentioning
confidence: 99%
“…Glycerophospholipids are an important part of the neuronal cell membrane structure and are involved in cell recognition and signal transduction. Therefore, the degradation of glycerophospholipids, which produces polyunsaturated fatty acids such as docosahexaenoicacid and arachidonic acid, may be a sign of brain damage [39,40]. A previous study has indicated that glycerophospholipid metabolism was signi cantly disrupted in stroke rats.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al reported that five metabolic markers, such as sphingomyelin (18:0/14:0), 1-methylpyrrolinium, phosphatidylcholine (18:0/18:0), lysophosphatidylcholine (18:0/0:0), and phosphatidylcholine (18:2/18:2), have good diagnostic and predictive ability. The change level of these metabolites is significantly related to ischemic stroke and provides early warning for the diagnosis of atherosclerosis-induced ischemic stroke ( 19 ). In acute ischemic stroke patients with severe intracranial arterial stenosis or occlusion, the asymmetrical prominent cortical vein sign might be a useful neuroimaging marker for predicting END ( 20 ).…”
Section: Discussionmentioning
confidence: 99%